2003
DOI: 10.1021/jp034043o
|View full text |Cite
|
Sign up to set email alerts
|

Combining Surface Plasmon Resonance and Quartz Crystal Microbalance for the in Situ Investigation of the Electropolymerization and Doping/Dedoping of Poly(pyrrole)

Abstract: An in situ combination of surface plasmon resonance (SPR) spectroscopy and quartz crystal microbalance (QCM) is used to study the electropolymerization and the doping/dedoping behavior of thin poly(pyrrole) (ppy) films in aqueous solutions. A mixed anion and cation exchange behavior is observed. The mass as determined with the QCM continuously increases during redox cycling. The combined QCM/SPR data reveal that this is caused by a relatively slow process occurring when ppy is in the oxidized (polaronic) state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…In Figure 7, the liquid can be represented as an additional infinitely thick layer above the film. The relation between the frequency change and the liquid was found to be able to be described by the real part of a complex frequency as demonstrated in [28]. A complex frequency was necessary because of the existence of losses which precluded a steady-state solution under purely mechanical excitation.…”
Section: Methodsmentioning
confidence: 97%
“…In Figure 7, the liquid can be represented as an additional infinitely thick layer above the film. The relation between the frequency change and the liquid was found to be able to be described by the real part of a complex frequency as demonstrated in [28]. A complex frequency was necessary because of the existence of losses which precluded a steady-state solution under purely mechanical excitation.…”
Section: Methodsmentioning
confidence: 97%
“…While each one of these transducers individually provides reliable qualitative curves during protein adsorption on their functionalized surfaces, extraction of quantitative physical parameters such as optical index, density, viscosity or water content requires modeling of the adsorbed layers [11]. The modeling includes multiple parameters which must be identified simultaneously: hence the need for the combination of (acoustic and optical) detection methods in a single instrument [12,13,14,15] to separate contributions as a same layer is reacting with the surface under investigation. Multiple investigators have identified such a combination of measurement methods as fruitful means of extracting independent physical properties of adsorbed layers, including the challenging combination of QCM and SPR [16,17,18,19,20] or comparing the results of successive experiments using different instruments [21,22,23,24], combining QCM and reflectometry [25] or measuring separately using the two techniques [26], or SAW and SPR [27].…”
Section: Introductionmentioning
confidence: 99%
“…The EQCM has been used extensively to study conducting polymers such as polypyrrole [4][5][6][7][8][9][10][11][12], poly(3,4-ethylenedioxythiopene) [12][13][14][15][16][17] and polyaniline [18][19][20][21][22][23][24][25][26][27]. This technique can be used for three main purposes in studying conducting polymers.…”
Section: Introductionmentioning
confidence: 99%